Engaging community partners to develop a culturally relevant resource guide for physical activity and nutrition - Bopp, Melissa; Fallon, Elizabeth A.; Bolton, Debra J.; Kahl, Daniel (My University, 2012)
Background: Community-based participatory research (CBPR) is an increasingly popular approach for obesity prevention efforts among ethnically diverse communities. There is limited documentation for practitioners and researchers attempting to initiate new CBPR partnerships within predominantly Hispanic communities. Objectives: To document the process underlying the initiation of a new CBPR collaborative and the development of a culturally relevant community resource guide for physical activity and nutrition. Setting: Three similar cities in southwest Kansas (40–60% Hispanic). The mission of local partner organizations included health or serving Hispanic community needs. Results: The CBPR collaborative combined community-specific cultural and historical information with physical activity and nutrition health education materials into community-specific resource guides. The guides were tailored to each community, culturally relevant, and highlighted free and low-cost resources. The guides were printed in English and Spanish and distributed to residents. Evaluation of the guide’s reach showed small-moderate dissemination, and good acceptance by community residents. Conclusion: Collaborative CBPR partnerships for obesity prevention can be formed by identifying a common, realistic and practical goal such as the creation of a community resource guide for physical activity and nutrition. The approach is relatively noninvasive for community members, requires minimal resources from community agencies and represents a positive first step in the CBPR approach to obesity and chronic disease prevention. Currently, the guide is being used in combination with other health promotion efforts to prevent obesity and related diseases. Furthermore, our CBPR partnership continues to thrive and provide the necessary foundation for health promotion efforts.
Keywords: Community-based; Hispanic; Physical Activity; Nutrition